Degradable plastic, container prepared from plastic and preparation method of container

By performing hydrogen oxide surface treatment on ultrafine coal powder and synthesis of calcium phosphate oligomers, combined with composite aerogel and porous carbon technology, the problems of poor gas barrier properties and poor compatibility of coal powder were solved, and a degradable plastic container with good gas barrier, mechanical properties and degradation properties were prepared.

CN119798933AActive Publication Date: 2025-04-11JIANGMEN JIANGDONG HUAPU PLASTIC CONTAINER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411850795.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Polyterephthalic acid-butadiester resin has poor gas barrier properties and cannot meet the application of plastic containers in beverages, food and other fields; as a photodegrading agent, coal powder can efficiently degrade polyvinyl alcohol, but its poor compatibility with organic polymer materials leads to a degradation performance.

Method used

Through ultrafine coal powder hydrogen oxide surface treatment, oxygen-containing functional groups are introduced to synthesize calcium phosphate oligomers to form composite aerogels, and porous carbon is adhered to the surface of modified corn stalk fibers to prepare a degradable plastic container with good gas barrier properties and mechanical properties.

Benefits of technology

The barrier properties and mechanical properties of plastic containers to gas are improved, while the degradation properties of the container are enhanced, solving the problem of poor compatibility between coal powder and organic polymer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190523280000131
    Figure BDA0005190523280000131
Patent Text Reader

Abstract

The invention discloses a degradable plastic, a container prepared from the plastic and a preparation method of the container, and belongs to the technical field of degradable plastic container processing.The preparation method of the degradable plastic comprises the following steps that poly (butylene adipate-co-terephthalate) resin, starch, composite aerogel, modified corn straw fibers, a lubricating agent and a plasticizer are mixed and stirred, and a mixture is obtained; uniformly stirring to obtain a mixture; and extruding and granulating the mixture to obtain the degradable plastic. The composite aerogel has the gas barrier property, the barrier property of the polyethylene terephthalate-butylene adipate plastic container to gas is improved, the composite aerogel has high mechanical strength, leakage of the modified superfine pulverized coal caused by poor mechanical property of sericin aerogel is avoided, the modified superfine pulverized coal is migrated and separated out in the plastic, and the modified superfine pulverized coal is recycled. The degradation performance of the plastic is influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of processing of degradable plastic containers, in particular to degradable plastics, containers prepared with the plastics and a preparation method thereof. Background Art

[0002] Degradable plastics refer to plastics that meet the requirements of use, whose performance remains unchanged during the shelf life, and which can be degraded into environmentally harmless substances under natural conditions after use. They include photodegradable plastics, biodegradable plastics, light / oxidation / biodegradable plastics, carbon dioxide-based biodegradable plastics, thermoplastic starch resin degradable plastics, etc. Degradable plastic containers are mainly used for plastic packaging of liquids or solids such as beverages, food, pickles, honey, dried fruits, and cooking oils; plastic containers are made of polyester, polyethylene, and polypropylene as raw materials, and after adding corresponding organic solvents, they are heated at high temperature and then made through plastic molds by blow molding, extrusion blow molding, or injection molding. However, polyester, polyethylene, and polypropylene raw materials cannot be degraded and can easily pollute the environment.

[0003] Plastic containers made from polybutylene terephthalate-adipate resin as raw material have good biodegradability, but polybutylene terephthalate-adipate resin has poor gas barrier properties and cannot meet the application of plastic containers in the fields of beverages, food, pickles, honey, dried fruits, cooking oils, etc. They can only be used as shopping bags, garbage bags, ground films and other film bag products without gas barrier requirements; coal powder is used as a photodegradation agent, and the oxygen-containing functional groups it contains produce free radicals under the action of ultraviolet light, which can induce the breakage of polyvinyl alcohol molecular chains and complete efficient degradation. However, coal powder as an inorganic material has poor compatibility with organic polymer materials and is easily precipitated, resulting in decreased degradation performance. Summary of the invention

[0004] The object of the present invention is to provide a degradable plastic, a container prepared with the plastic and a preparation method thereof: ultrafine coal powder is subjected to surface treatment with hydrogen peroxide to introduce more oxygen-containing functional groups, thereby improving the activity of the ultrafine coal powder and facilitating the synthesis of calcium phosphate oligomers in the pores and surface of the ultrafine coal powder; nanometer-sized calcium phosphate oligomers are synthesized on the surface and pores of the pretreated ultrafine coal powder to block the pores of the ultrafine coal powder and prevent the porous structure contained in the ultrafine coal powder from easily absorbing moisture; sericin powder, naringin and modified ultrafine coal powder are mixed to form a composite aerogel, and the formed composite aerogel has high heat resistance stability and gas barrier performance; porous carbon adheres to the surface of corn stalk fiber modified with polydopamine, microorganisms can contact the corn stalk fiber through the pores of the porous carbon, and then decompose the corn stalk fiber, and the excellent aspect ratio of the corn stalk fiber is added to the degradable plastic, and the prepared plastic container has good mechanical properties.

[0005] The technical problems to be solved by the present invention are as follows: polybutylene terephthalate-adipate resin has poor gas barrier properties and cannot meet the application requirements of plastic containers in the fields of beverages, foods, pickles, honey, dried fruits, edible oils, etc.; coal powder, as a photodegradation agent, contains oxygen-containing functional groups that generate free radicals under the action of ultraviolet light, which can induce the breakage of polyvinyl alcohol molecular chains and achieve efficient degradation; however, coal powder, as an inorganic material, has poor compatibility with organic polymer materials and is easily precipitated, resulting in decreased degradation performance.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The method for preparing degradable plastics comprises the following steps:

[0008] S1. Mix polybutylene terephthalate-adipate resin, starch, composite aerogel, modified corn straw fiber, lubricant and plasticizer, stir evenly to obtain a mixture.

[0009] S2. The mixed material is extruded and granulated to obtain a degradable plastic.

[0010] Furthermore, the weight average molecular weight of the polybutylene terephthalate-adipate resin is 2.5×10 5 -3.5×10 5 g / mol.

[0011] Furthermore, the plasticizer is selected from one of epoxidized soybean oil, triethyl citrate, glycerol and polyethylene glycol.

[0012] Furthermore, the lubricant is selected from erucamide or ethylene bisstearamide.

[0013] Furthermore, a twin-screw extruder is used for extrusion, the temperature of the first melting section is 145-155°C, the temperature of the second melting section is 140-150°C, the temperature of the third melting section is 130-140°C, the screw speed is 80-100rpm, and the extrusion port temperature is 118-122°C.

[0014] Furthermore, the mass ratio of polybutylene terephthalate-adipate resin, starch, composite aerogel, modified corn straw fiber, lubricant and plasticizer is (60-80):(30-40):(5-7):(4-6):(0.3-1):(3-5).

[0015] Furthermore, the starch is corn starch.

[0016] Furthermore, the composite aerogel is prepared by a mixed reaction of modified ultrafine coal powder, sericin powder and naringin.

[0017] Furthermore, the modified ultrafine coal powder is prepared by subjecting the ultrafine coal powder to surface treatment with hydrogen oxide and then reacting the surface with a calcium source and phosphoric acid.

[0018] Furthermore, the ultrafine coal powder has a particle size of 1-5 μm and a pore size of 100-300 nm.

[0019] Furthermore, the mass fraction of hydrogen peroxide is 10-15%.

[0020] Furthermore, the calcium source is selected from calcium chloride dihydrate or hydrated calcium nitrate.

[0021] Furthermore, the composite aerogel is specifically prepared by the following steps:

[0022] A1. After washing and drying the ultrafine coal powder, the washed ultrafine coal powder is added to a 10-15% mass fraction hydrogen peroxide solution, stirred at 80°C for 3h, filtered, washed and dried to obtain pretreated ultrafine coal powder;

[0023] A2. The pretreated ultrafine coal powder and the calcium source were added to ethanol, stirred evenly, triethylamine and phosphoric acid were added, stirred and reacted at 45°C for 5 hours, centrifuged at 8000 rpm for 5 minutes, washed with ethanol 3 times, washed with deionized water 3 times, and dried in an oven at 60°C for 10 minutes to obtain modified ultrafine coal powder;

[0024] A3. Add sericin powder, modified ultrafine coal powder and naringin to deionized water, heat at 45°C until the sericin powder is completely dissolved, continue stirring and reacting for 30 minutes, place in a freezer, and freeze-dry at -20°C for 2 hours to obtain a composite aerogel.

[0025] Furthermore, in the above-mentioned reaction process A1, hydrogen peroxide has a strong oxidizing property and can react with impurities on the surface of the coal powder to remove the surface impurities and introduce more oxygen-containing functional groups to improve the activity of the coal powder, which is beneficial to the synthesis of calcium phosphate oligomers in the pores and surface of the ultrafine coal powder and enhance the degradation performance of the ultrafine coal powder on plastic containers.

[0026] Furthermore, during the above-mentioned A2 reaction process, the surface of the pretreated ultrafine coal powder contains a porous structure and has good adsorption performance. The oxygen-containing functional groups on its surface can combine with calcium ions in the calcium source, so that the calcium ions are adsorbed in the pores of the ultrafine coal powder, and the phosphate ions can form calcium phosphate complexes with the calcium ions through electrostatic bonding. Under the action of the catalyst triethylamine, the generated calcium phosphate complexes interact and arrange with each other to form nano-sized calcium phosphate oligomers, thereby realizing the synthesis of nano-sized calcium phosphate oligomers on the surface of the pretreated ultrafine coal powder.

[0027] Furthermore, in the above-mentioned A3 reaction process, the sericin powder is heated at 45°C to form a sericin solution, and the hydroxyl and carboxyl groups contained in the sericin can be combined with the oxygen-containing functional groups in naringin through chemical bonds to form a cross-linked network structure, and the phosphate and calcium ions contained on the surface of the modified ultrafine coal powder can also participate in the reaction to form a composite aerogel.

[0028] Furthermore, in step A1, the ratio of the washed ultrafine coal powder to the hydrogen peroxide solution is (5-7) g: (45-55) mL.

[0029] Furthermore, in step A2, the ratio of the amount of pretreated ultrafine coal powder, calcium source, ethanol, triethylamine and phosphoric acid is (2-4) g: (1-1.2) g: (55-65) mL: (0.1-0.3) g: (1-2) g.

[0030] Furthermore, in step A3, the ratio of sericin powder, modified ultrafine coal powder, naringin and deionized water is (7-9) g: (2-3) g: (2.2-2.4) g: (70-90) mL.

[0031] Furthermore, the sericin powder is specifically prepared by the following steps:

[0032] The silkworm cocoons are cut into blocks, placed in deionized water, and sterilized under high pressure at a temperature of 120-122° C. and a pressure of 0.05-0.15 MPa for 25-35 min, and then the sericin aqueous solution is collected and freeze-dried to obtain sericin powder.

[0033] Among them, the silk cocoons are cut into blocks and sterilized under high temperature and pressure. The cell membrane of the bacteria in the cocoons is affected by the pressure, which causes the cell membrane to rupture and the substance inside the cell to leak out. The high temperature can destroy the protein and nucleic acid of the bacteria, causing them to lose their biological activity and replication ability. The bacteria, viruses and other microorganisms in the cocoons are killed under the action of high temperature and high pressure, achieving the purpose of sterilization, ensuring the purity of the sericin, and retaining its original structure and properties, providing high-quality raw materials for subsequent processing and application.

[0034] Furthermore, the ratio of silkworm cocoons to deionized water is (4-6) g:(45-55) mL.

[0035] Furthermore, the modified corn straw fiber is prepared by modifying the corn straw fiber with polydopamine and then mixing it with porous carbon.

[0036] Furthermore, the diameter of corn stalk fiber is 20-50 μm, the length is 2-5 mm, the water absorption rate is 25-35%, and the density is 1.2-1.4 g / cm 3 .

[0037] Furthermore, the porous carbon has a pore size of 20-100 nm and a particle size of 0.2-5 μm.

[0038] Furthermore, the modified corn stalk fiber is prepared by the following steps:

[0039] B1. Add corn straw fiber to Tris-HCl buffer, stir evenly, add dopamine, stir for 4-6 hours, filter, wash with deionized water, and dry to obtain polydopamine-modified corn straw fiber.

[0040] B2. Add polydopamine-modified corn straw fiber and porous carbon into deionized water, stir evenly, let stand, filter, wash and dry to obtain modified corn straw fiber.

[0041] Furthermore, during the above-mentioned B1 reaction, in the Tris-HCl buffer, dopamine can self-polymerize on the surface of the corn straw fiber to form polydopamine, so that the corn straw fiber has better adhesion, which is conducive to the adhesion of porous carbon on the surface of the corn straw fiber.

[0042] Furthermore, during the above B2 reaction process, the polydopamine layer on the surface of the polydopamine-modified corn straw fiber has good adhesion and contains a large amount of phenolic hydroxyl groups, thereby being able to adhere the porous carbon to the surface of the polydopamine-modified corn straw fiber.

[0043] Furthermore, in step B1, the ratio of corn straw fiber, Tris-HCl buffer and dopamine is (1-2) g: (50-60) mL: (0.5-0.9) g.

[0044] Furthermore, in step B2, the ratio of polydopamine-modified corn straw fiber, porous carbon and deionized water is (1-2) g: (0.6-0.8) g: (25-35) mL.

[0045] Furthermore, the container made of degradable plastic includes the following preparation steps:

[0046] The degradable plastic is added into the hopper of the injection machine, melted at 140-150°C, injected into the tube blank mold, kept at 165-175°C for 20-30 minutes, cooled to room temperature, and opened to obtain the degradable plastic container.

[0047] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) In the technical solution of the present invention, the ultrafine coal powder is a photodegradation agent with a macromolecular aromatic lamellar structure as the main body, and its outer edge is connected to some weak bonds and some oxygen-containing functional groups. The hydroxyl group, phenolic hydroxyl group and weak bond contained in the ultrafine coal powder are easily dissociated into free radicals under ultraviolet irradiation. In addition, in the presence of oxygen, the ultrafine coal powder can react with oxygen to generate peroxides and peroxy radicals, which are further decomposed to generate oxidative free radicals, which can participate in the degradation of polybutylene terephthalate-adipate plastic containers; the ultrafine coal powder is surface treated with hydrogen peroxide, and hydrogen peroxide has a strong oxidizing property, which can react with impurities on the surface of the coal powder to remove surface impurities, and introduce more oxygen-containing functional groups, thereby improving the activity of the ultrafine coal powder, facilitating the synthesis of calcium phosphate oligomers in the pores and surface of the ultrafine coal powder, and enhancing the degradation performance of the ultrafine coal powder on plastic containers.

[0049] (2) In the technical solution of the present invention, nano-sized calcium phosphate oligomers are synthesized on the surface and in the pores of the pretreated ultrafine coal powder. On the one hand, the pores of the ultrafine coal powder can be blocked to prevent the porous structure of the ultrafine coal powder from absorbing moisture easily and affecting the performance of the degradable plastic container. On the other hand, the formed nano-sized calcium phosphate oligomers have high mechanical strength, which cooperates with the pretreated ultrafine coal powder to enhance the mechanical properties of the degradable plastic container.

[0050] (3) In the technical solution of the present invention, sericin powder, naringin, and modified ultrafine coal powder are mixed to form a composite aerogel. The formed composite aerogel has high heat resistance stability and gas barrier performance, which improves the gas barrier property of the polybutylene terephthalate-adipate plastic container. The modified ultrafine coal powder and naringin are embedded in the composite aerogel, which increases the crosslinking density of the sericin composite aerogel and improves the mechanical strength. The poor mechanical properties of the sericin aerogel lead to leakage of the modified ultrafine coal powder and affect the gas barrier property of the composite aerogel, so that the modified ultrafine coal powder migrates and precipitates in the plastic, affecting the degradation performance of the plastic. In addition, the formed composite aerogel has high heat resistance stability, which avoids the decomposition of sericin powder and naringin during the melting process of the plastic.

[0051] (4) In the technical scheme of the present invention, porous carbon is adhered to the surface of polydopamine-modified corn straw fiber. On the one hand, the porous carbon can block the direct contact between the corn straw fiber and the external environment, reduce the corn straw fiber's absorption of moisture in the environment, and avoid the corn straw fiber's swelling due to water absorption, which leads to a decrease in the mechanical properties of the plastic container. The porous carbon is coated on the surface of the corn straw fiber to increase the surface roughness of the corn straw fiber and increase the bonding force between the corn straw fiber and the plastic matrix. On the other hand, the porous structure of the porous carbon can be connected to the outside world, and microorganisms can contact the corn straw fiber through the pores of the porous carbon, thereby decomposing the corn straw fiber without affecting the degradation performance of the corn straw fiber. In addition, the excellent aspect ratio of the corn straw fiber is added to the degradable plastic to prepare a plastic container with good mechanical properties. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The raw materials used in the embodiments of the present invention are as follows:

[0054] Calcium chloride dihydrate, triethylamine, phosphoric acid (purchased from Sinopharm Chemical Reagent Co., Ltd.); naringin (purity of 98%, purchased from Xi'an Zhanxun Biotechnology Co., Ltd.); Tris-HCl buffer (purity of 99%, purchased from Wuhan Desheng Biochemical Technology Co., Ltd.); dopamine (purchased from Shanghai Myrrel Biochemical Technology Co., Ltd.).

[0055] The weight average molecular weight of polybutylene terephthalate adipate resin is 3×10 5 g / mol.

[0056] The ultrafine coal powder had a particle size of 3 μm and a pore size of 200 nm and was purchased from Pingdingshan Zhurun ​​Energy Co., Ltd.

[0057] The porous carbon had a pore size of 20-100 nm and a particle size of 0.2-5 μm, and was purchased from Jinan Shengquan Group Co., Ltd.

[0058] The diameter of corn straw fiber is 35 μm, the length is 3 mm, the water absorption rate is 30%, and the density is 1.3 g / cm 3 .

[0059] The starch is corn starch.

[0060] Silkworm cocoons were purchased from Suzhou Huguangshanse Velvet Development Co., Ltd.

[0061] The silk gel powder is specifically prepared by the following steps:

[0062] 5 g of silkworm cocoons were cut into blocks, placed in 55 mL of deionized water, and sterilized under high pressure at a temperature of 121° C. and a pressure of 0.1 MPa for 30 min to dissolve the sericin. The sericin aqueous solution was collected and freeze-dried at -20° C. for 30 min to obtain sericin powder.

[0063] Example 1 The composite aerogel is prepared by the following steps:

[0064] A1. The ultrafine coal powder was washed with water three times, dried in an oven at 60°C for 10 min, 6 g of the washed ultrafine coal powder was added to 50 mL of a 13% hydrogen peroxide solution, stirred at 80°C for 3 h, filtered, washed with deionized water three times, and dried in an oven at 70°C for 10 min to obtain pretreated ultrafine coal powder;

[0065] A2. 3 g of pretreated ultrafine coal powder and 1.1 g of calcium chloride dihydrate were added to 60 mL of ethanol, stirred for 30 min, and then 0.2 g of triethylamine and 1.5 g of phosphoric acid were added. After stirring at 45 ° C for 5 h, the mixture was centrifuged at 8000 rpm for 5 min, filtered, washed with ethanol 3 times, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain modified ultrafine coal powder;

[0066] A3. Add 8 g of sericin powder, 2.5 g of modified ultrafine coal powder and 2.3 g of naringin to 80 mL of deionized water, heat at 45°C until the sericin powder is completely dissolved, continue stirring and reacting for 30 minutes, place in a freezer, and freeze-dry at -20°C for 2 hours to obtain a composite aerogel.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is that the pretreated ultrafine coal powder is replaced by ultrafine coal powder, and the remaining steps and raw materials are synchronized with Example 1.

[0068] A1. Add 3 g of ultrafine coal powder and 1.1 g of calcium chloride dihydrate to 60 mL of ethanol, stir for 30 min, add 0.2 g of triethylamine and 1.5 g of phosphoric acid, stir at 45 ° C for 5 h, centrifuge at 8000 rpm for 5 min, filter, wash 3 times with ethanol, wash 3 times with deionized water, and dry in an oven at 60 ° C for 10 min to obtain modified ultrafine coal powder;

[0069] A2. Add 8 g of sericin powder, 2.5 g of modified ultrafine coal powder and 2.3 g of naringin to 80 mL of deionized water, heat at 45°C until the sericin powder is completely dissolved, continue stirring and reacting for 30 minutes, place in a freezer, and freeze-dry at -20°C for 2 hours to obtain a composite aerogel.

[0070] Comparative Example 2 The difference between this comparative example and Example 1 is that the modified ultrafine coal powder is replaced by pretreated ultrafine coal powder, and the remaining steps and raw materials are the same as Example 1.

[0071] A1. The ultrafine coal powder was washed with water three times, dried in an oven at 60°C for 10 min, 6 g of the washed ultrafine coal powder was added to 50 mL of a 13% hydrogen peroxide solution, stirred at 80°C for 3 h, filtered, washed with deionized water three times, and dried in an oven at 70°C for 10 min to obtain pretreated ultrafine coal powder;

[0072] A2. Add 8 g of sericin powder, 2.5 g of pretreated ultrafine coal powder and 2.3 g of naringin to 80 mL of deionized water, heat at 45°C until the sericin powder is completely dissolved, continue stirring and reacting for 30 minutes, place in a freezer, and freeze-dry at -20°C for 2 hours to obtain a composite aerogel.

[0073] Comparative Example 3 The difference between this comparative example and Example 1 is that no naringin is added, and the remaining steps and raw materials are the same as Example 1.

[0074] A1. The ultrafine coal powder was washed with water three times, dried in an oven at 60°C for 10 min, 6 g of the washed ultrafine coal powder was added to 50 mL of a 13% hydrogen peroxide solution, stirred at 80°C for 3 h, filtered, washed with deionized water three times, and dried in an oven at 70°C for 10 min to obtain pretreated ultrafine coal powder;

[0075] A2. 3 g of pretreated ultrafine coal powder and 1.1 g of calcium chloride dihydrate were added to 60 mL of ethanol, stirred for 30 min, and then 0.2 g of triethylamine and 1.5 g of phosphoric acid were added. After stirring at 45 ° C for 5 h, the mixture was centrifuged at 8000 rpm for 5 min, filtered, washed with ethanol 3 times, washed with deionized water 3 times, and dried in an oven at 60 ° C for 10 min to obtain modified ultrafine coal powder;

[0076] A3. Add 8 g of sericin powder and 2.5 g of modified ultrafine coal powder into 80 mL of deionized water, heat at 45°C until the sericin powder is completely dissolved, continue stirring and reacting for 30 minutes, place in a freezer, and freeze-dry at -20°C for 2 hours to obtain a composite aerogel.

[0077] Example 2 The modified corn straw fiber is prepared by the following steps:

[0078] B1. Add 1.5 g corn straw fiber to 55 mL Tris-HCl buffer, stir evenly, add 0.7 g dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified corn straw fiber.

[0079] B2. Add 1.5 g polydopamine-modified corn straw fiber and 0.7 g porous carbon into 30 mL deionized water, stir evenly, let stand for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 70 °C for 10 min to obtain modified corn straw fiber.

[0080] Comparative Example 4 The difference between this comparative example and Example 2 is that the polydopamine-modified corn straw fiber is replaced by corn straw fiber, and the remaining steps and raw materials are the same as Example 2.

[0081] 1.5 g corn straw fiber and 0.7 g porous carbon were added to 30 mL deionized water, stirred evenly, allowed to stand for 10 min, filtered, washed with deionized water three times, and dried in an oven at 70 °C for 10 min to obtain modified corn straw fiber.

[0082] Comparative Example 5 The difference between this comparative example and Example 2 is that porous carbon is not added, and the remaining steps and raw materials are the same as Example 2.

[0083] 1.5 g corn straw fiber was added to 55 mL Tris-HCl buffer, stirred evenly, 0.7 g dopamine was added, stirred for 4 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 °C for 10 min to obtain modified corn straw fiber.

[0084] Embodiment 3 The preparation method of the degradable plastic container comprises the following steps:

[0085] S1. Mix polybutylene terephthalate-adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 2, erucic acid amide, and epoxy soybean oil, stir evenly, and obtain a mixture.

[0086] S2. The mixed material is extruded and granulated to obtain a degradable plastic.

[0087] S3. Add the degradable plastic into the hopper of the injection machine, melt it at 140°C, inject it into the tube blank mold, keep it at 165°C for 20 minutes, cool it to room temperature, open the mold, and obtain the degradable plastic container.

[0088] Among them, the mass ratio of polybutylene terephthalate-adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 2, erucic acid amide, and epoxy soybean oil is 60:30:5:4:0.3:3.

[0089] A twin-screw extruder was used for extrusion, with the temperature of the first melting section being 145°C, the temperature of the second melting section being 140°C, the temperature of the third melting section being 130°C, the screw speed being 80 rpm, and the extrusion port temperature being 118°C.

[0090] Embodiment 4 The preparation method of the degradable plastic container comprises the following steps:

[0091] S1. Mix polybutylene terephthalate-adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 2, ethylene bisstearamide, and triethyl citrate, stir evenly, and obtain a mixture.

[0092] S2. The mixed material is extruded and granulated to obtain a degradable plastic.

[0093] S3. Add the degradable plastic into the hopper of the injection machine, melt it at 145°C, inject it into the tube blank mold, keep it at 170°C for 25 minutes, cool it to room temperature, open the mold, and obtain the degradable plastic container.

[0094] Among them, the mass ratio of polybutylene terephthalate-adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 2, ethylene bisstearamide, and triethyl citrate is 70:35:6:5:0.6:4.

[0095] A twin-screw extruder was used for extrusion, with the temperature of the first melting section being 150°C, the temperature of the second melting section being 145°C, the temperature of the third melting section being 135°C, the screw speed being 90 rpm, and the extrusion port temperature being 120°C.

[0096] Embodiment 5 The preparation method of the degradable plastic container comprises the following steps:

[0097] S1. Mix polybutylene terephthalate adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 2, erucic acid amide, and glycerol, stir evenly, and obtain a mixture.

[0098] S2. The mixed material is extruded and granulated to obtain a degradable plastic.

[0099] S3. Add the degradable plastic into the hopper of the injection machine, melt it at 150°C, inject it into the tube blank mold, keep it at 175°C for 30 minutes, cool it to room temperature, open the mold, and obtain the degradable plastic container.

[0100] Among them, the mass ratio of polybutylene terephthalate-adipate resin, corn starch, the composite aerogel prepared in Example 1, the modified corn straw fiber prepared in Example 1, erucamide, and glycerol is 80:40:7:6:1:5.

[0101] A twin-screw extruder was used for extrusion, with the temperature of the first melting section being 155°C, the temperature of the second melting section being 150°C, the temperature of the third melting section being 140°C, the screw speed being 100 rpm, and the extrusion port temperature being 122°C.

[0102] Comparative Example 6 The difference between this comparative example and Example 4 is that the composite aerogel prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.

[0103] Comparative Example 7 The difference between this comparative example and Example 4 is that the composite aerogel prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.

[0104] Comparative Example 8 The difference between this comparative example and Example 4 is that the composite aerogel prepared in Example 1 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0105] Comparative Example 9 The difference between this comparative example and Example 4 is that the modified corn straw fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.

[0106] Comparative Example 10 The difference between this comparative example and Example 4 is that the modified corn straw fiber prepared in Example 2 is replaced by the material prepared in Comparative Example 5, and the remaining steps are synchronized with Example 4.

[0107] The performance of the degradable plastic containers prepared in Examples 3-5 and Comparative Examples 6-10 is now tested;

[0108] Tensile strength test: The tensile strength of the biodegradable plastic container prepared above was tested according to the standard GB / T 1040.1-2018 test method.

[0109] Elongation at break test: The elongation at break of the biodegradable plastic container prepared above was tested according to standard GB / T 1040.1-2018.

[0110] Degradation performance test: The degradable plastic container prepared above was dried at 90°C to constant weight, 10 cm thick soil was laid in a beaker, the water activity was adjusted to 15%, and the soil was evenly buried, and ultraviolet light (wavelength of 300 nm) was applied to the beaker. After 15 days, the sample to be tested was taken out, the surface was rinsed with water, and then dried at 90°C to constant weight, and the weight loss rate was calculated;

[0111] Barrier property test: The barrier property of the biodegradable plastic container prepared above was tested in accordance with the national standard GB / T 31354-2014 "Test method for oxygen permeability of packages and containers - Coulometric test method". The test results are shown in Table 1 below:

[0112] Table 1

[0113]

[0114] It can be seen from the data in Table 1 that in Comparative Example 6, the pretreated ultrafine coal powder is replaced with a composite aerogel prepared from ultrafine coal powder and added to a degradable plastic container, and its mechanical properties and degradability are reduced. This may be because the ultrafine coal powder is surface treated with hydrogen peroxide, which is beneficial to the synthesis of calcium phosphate oligomers in the pores and surface of the ultrafine coal powder, thereby enhancing the degradation performance of the ultrafine coal powder on the plastic container. However, the surface of the ultrafine coal powder lacks oxygen-containing functional groups and cannot achieve this effect, so the mechanical properties and degradability are reduced.

[0115] In Comparative Example 7, the composite aerogel prepared by replacing the modified ultrafine coal powder with pretreated ultrafine coal powder was added to a degradable plastic container, and its mechanical properties decreased. This may be because nano-sized calcium phosphate oligomers were synthesized on the surface and in the pores of the pretreated ultrafine coal powder to prevent the porous structure contained in the ultrafine coal powder from being easily hygroscopic, and the formed nano-sized calcium phosphate oligomers have higher mechanical strength. The pretreated ultrafine coal powder lacks nano-sized calcium phosphate oligomers and cannot achieve this effect, so its mechanical properties decrease.

[0116] In Comparative Example 8, the composite aerogel prepared by the composite filler prepared without adding naringin was added to the degradable plastic container, and its mechanical properties, degradation properties and barrier properties decreased. This may be because naringin was embedded in the composite aerogel, which increased the crosslinking density of the sericin composite aerogel, improved the mechanical strength, and avoided the leakage of the modified ultrafine coal powder due to the poor mechanical properties of the sericin aerogel, which migrated and precipitated in the plastic and affected the degradation properties of the plastic. In the absence of naringin, this effect could not be achieved, and thus the mechanical properties and degradation properties decreased.

[0117] In Comparative Example 9, modified corn straw fibers prepared by replacing polydopamine-modified corn straw fibers with corn straw fibers were added to a degradable plastic container, and the mechanical properties thereof decreased. This may be because polydopamine was self-polymerized on the surface of the corn straw fibers, which gave the corn straw fibers better adhesion, facilitating the adhesion of porous carbon on the surface of the corn straw fibers. The porous carbon can block direct contact between the corn straw fibers and the external environment, reduce the corn straw fibers' absorption of moisture in the environment, and prevent the corn straw fibers from absorbing water and swelling, leading to a decrease in the mechanical properties of the plastic container. Without polydopamine-modified corn straw fibers, this effect could not be achieved, and thus the mechanical properties decreased.

[0118] In Comparative Example 10, the modified corn straw fiber prepared without adding porous carbon was added to the biodegradable plastic container, and its mechanical properties decreased. This may be because the porous carbon adhered to the surface of the polydopamine-modified corn straw fiber, which can reduce the corn straw fiber's absorption of moisture in the environment, and the porous carbon was coated on the surface of the corn straw fiber, which increased the surface roughness of the corn straw fiber and increased the bonding force between the corn straw fiber and the plastic matrix. Without porous carbon, this effect could not be achieved, and thus the mechanical properties decreased.

[0119] The data in Table 1 show that the degradable plastic containers prepared in Examples 3-5 meet the test performance requirements, while the degradable plastic containers prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the degradable plastic containers prepared in the present invention have good mechanical properties, degradability and gas barrier properties.

[0120] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0121] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a degradable plastic, characterized in that: The following steps are involved: S1. The polybutylene terephthalate resin, starch, composite aerogel, modified corn straw fiber, lubricant, and plasticizer are mixed and stirred to obtain a mixture; S2. The mixed material is extruded and granulated to obtain a degradable plastic; The composite aerogel is prepared by mixing modified ultrafine coal powder, sericin powder and naringin; The modified ultrafine coal powder is prepared by reacting the ultrafine coal powder with a calcium source and phosphoric acid after the ultrafine coal powder is subjected to surface treatment with hydrogen oxide; The modified corn stalk fiber is prepared by modifying the corn stalk fiber with polydopamine and then mixing the modified corn stalk fiber with porous carbon.

2. The method for preparing a degradable plastic according to claim 1, characterized in that: The particle size of the ultrafine coal powder is 1-5 μm, and the pore size is 100-300 nm; the mass fraction of the hydrogen peroxide is 10-15%.

3. The method for preparing the degradable plastic according to claim 1, characterized in that: The sericin powder is specifically prepared by the following steps: cutting silkworm cocoons into blocks, placing them in deionized water, sterilizing them under high pressure at a temperature of 120-122° C. and a pressure of 0.05-0.15 MPa for 25-35 minutes, collecting the sericin solution, and freeze-drying the sericin solution to obtain sericin powder.

4. The method for preparing a degradable plastic according to claim 1, characterized in that: The calcium source is selected from calcium chloride dihydrate or hydrated calcium nitrate.

5. The method for preparing the degradable plastic according to claim 1, characterized in that: The corn stalk fiber has a diameter of 20-50 μm, a length of 2-5 mm, a water absorption rate of 25-35%, and a density of 1.2-1.4 g / cm 3 ; The pore size of the porous carbon is 20-100nm and the particle size is 0.2-5μm.

6. The method for preparing a degradable plastic according to claim 1, characterized in that: The weight average molecular weight of the polybutylene terephthalate-adipate resin is 2.5×10 5 -3.5×10 5 g / mol.

7. The method for preparing a degradable plastic according to claim 1, characterized in that: The plasticizer is selected from one of epoxidized soybean oil, triethyl citrate, glycerol and polyethylene glycol; the lubricant is selected from erucamide or ethylene bisstearamide.

8. The method for preparing a degradable plastic according to claim 1, characterized in that: The extrusion is carried out using a twin-screw extruder, the temperature of the first melting section is 145-155°C, the temperature of the second melting section is 140-150°C, the temperature of the third melting section is 130-140°C, the screw speed is 80-100rpm, and the extrusion port temperature is 118-122°C.

9. A degradable plastic obtained by the method for preparing a degradable plastic as claimed in any one of claims 1 to 8.

10. A container made of the degradable plastic obtained according to claim 9, characterized in that: The method comprises the following preparation steps: The degradable plastic is added into the hopper of the injection machine, melted at 140-150°C, injected into the tube blank mold, kept at 165-175°C for 20-30 minutes, cooled to room temperature, and opened to obtain the degradable plastic container.

Citation Information

Patent Citations

  • Compostable antibacterial material for recyclable packaging products and preparation method thereof

    CN115651376A

  • Degradable composite polyethylene plastic and preparation method thereof

    CN118006019A

  • Carbon fiber reinforced plastics using polydopamine and the manufacturing method thereof

    KR1020140121019A